Design, Development and Calibration of an Integrated Thin Ring Drawbar Pull Transducer for an Agricultural Tractor (University of Khartoum Engineering Journal, 2022)
The objective of this research work is to design, develop and calibrate an integrated thing ring drawbar transducer for measuring the horizontal drawbar pull of an agricultural tractor. The transducer is based on a thin proof ring that forms an integral part of the drawbar element with strain gauges bonded on the inside and the outside curvature of the proof ring. The strain gauges are arranged in a full bridge constant volt circuitry and interfaced to a data acquisition system. Static calibration tests on the transducer showed high degree of linearity between applied load and output volt with coefficient of correlation R2 equal to 0.9968. The transducer measurements accuracy was within the acceptable range limits with measurement errors not more than 0.67% of the measured force magnitudes under the static measurements. The data acquisition system was able to successfully scan and recorded the transducer signals as programmed. The developed transducer can be a part of complete instrumentation system to be used for developing comprehensive information database on power and energy demand of various tractor and implement field operation in Sudan.